Effect of constant and varying mixture properties in spark ignition engine combustion process using computational fluid dynamics - Omar, Arshad (2012)
This project deals with the numerical setup about the effect of different mixture properties of premixed combustion material using Computational Fluid Dynamic (CFD). Mitsubishi Magma 4G15 is used as the base line engine design for the simulation model. 2000 revolution per minute (rpm) and 1000 iterations are set as the tested speed and the number of iterations per time step respectively. The simulation is started right before the spark ignited and when both valves are closed. The model is simulated at different mixture properties which are constant and varying mixture properties. The constant mixture properties value is taken from previous study. While the varying mixture properties is simulated using kinetic theory where only specific heat, thermal conductivity, and viscosity are varied. Case 1 is set as the constant mixture properties and also as the benchmark case. Case 2 until case 5 is the varying mixture properties with different value of L-J parameters. Case 1 gives only 2.19% of deviation from the experimental result on the peak pressure value and 25% deviation on the peak pressure timing. Meanwhile, for case 2 until case 5, they give as much as 22.34% until 45% deviation on peak pressure value and 100% until 162.5% deviations on the peak pressure timing. The key parameter that caused the results are the L-J parameters, mass fraction burned, and turbulence flame speed. The inaccuracy of the turbulence speed is mostly based on laminar flame speed, thermal conductivity, and specific heat. So, the study of L-J parameter is needed to ensure the perfect result in using kinetic theory approach.